2010
DOI: 10.1111/j.1537-2995.2009.02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive therapy by transfusing expanded donor murine natural killer T cells can suppress acute graft‐versus‐host disease in allogeneic bone marrow transplantation

Abstract: The results suggest that donor iNKT cells could alleviate GVHD symptoms and prolong survival after MHC-mismatched allogeneic BMT, which may be associated with the maintenance in IL-4 levels. These findings indicate that the therapy based on iNKT cells from MHC-mismatched donors has great potential in protection against GVHD after allogeneic hematopoietic stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Study of iNKT cells in donor PBSC grafts provides a unique opportunity to accurately identify and enumerate iNKT cells as well as other effector and regulatory immune cells in humans and thus define their role in aGVHD, a major source of morbidity and mortality in allogeneic HSCT. We addressed this important question by studying the effect of iNKT cells contained in G-CSF-mobilized PBSC grafts on the basis of evidence from the murine model showing that (1) G-CSF-mobilized iNKT cells protect from aGVHD and enhance the GVL effect 14 and (2) adoptively transferred, unmanipulated, 17 or in vitro ␣GC-expanded 15,16 iNKT cells can ameliorate aGVHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Study of iNKT cells in donor PBSC grafts provides a unique opportunity to accurately identify and enumerate iNKT cells as well as other effector and regulatory immune cells in humans and thus define their role in aGVHD, a major source of morbidity and mortality in allogeneic HSCT. We addressed this important question by studying the effect of iNKT cells contained in G-CSF-mobilized PBSC grafts on the basis of evidence from the murine model showing that (1) G-CSF-mobilized iNKT cells protect from aGVHD and enhance the GVL effect 14 and (2) adoptively transferred, unmanipulated, 17 or in vitro ␣GC-expanded 15,16 iNKT cells can ameliorate aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…To directly show that human iNKT cells are able to inhibit the alloresponse, as shown in murine studies in which ␣GC-expanded donor iNKT cells ameliorate experimental aGVHD, 15,16 we tested the ability of ␣GC-expanded human CD4 ϩ and CD4 Ϫ iNKT-cell subsets to regulate the MLR, an in vitro correlate of the alloresponse. For this purpose, highly purified (supplemental Figure 4) normal donor CD4 ϩ and CD4 Ϫ NKT cells, autologous to responder T cells, were added to the allogeneic, HLA-mismatched MLR at an iNKT-to-responder (R) ratio of 10:1.…”
Section: Function Of Cd4 ؊ Inkt Cells In the In Vitro Alloresponsementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated IL-4 levels have been described in acute GvHD, 43,44 and the beneficial effect of natural killer cells on GvHD seems to be IL-4 dependent. [45][46][47][48] We found renal IL-4 expression to be significantly elevated in allogeneic LIP animals compared to syngeneic animals. Allogeneic HIP animals only showed a trend toward higher expression.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, donor iNKTs expanded in vitro by stimulation with αGC attenuate GvHD. 90,91 Furthermore, in vivo injection of αGC or OCH (a homologue of αGC) attenuates GvHD severity via host iNKT production of IL-4 and Th2 polarization of donor T cells. 89 However, contradictory to these favorable observations, another study 92 reported that the administration of αGC (but not its N-acyl variant, C20:2) induces hyper-acute GvHD and rapid mortality in mice.…”
Section: Human Cd4mentioning
confidence: 99%